Perception of the Secondary Level Students Regarding the Examination Ethics - Panday, Nikesh (Ganeshman Darpan, 2024)
In the study entitled Perception of the secondary level students regarding the examination ethics in Nepal, the Grade XII students expressed their opinions on examination ethics. The Grade XII students from a school in the Kathmandu district were randomly chosen to participate in the survey. The study found that the students were aware of exam ethics. They agreed that sustaining examination ethics in Nepal is complicated. 51.7% of the students favored implementing rules to follow examination ethics. 89.7% of the students decided on a fair examination.40.5% said their parents, teachers, and stakeholders favored cheating, whereas 59.5% followed the examination ethics. However, maintaining the ethics includes being aware of impersonation and cheating. Most students perceived the examination as complex, so keeping ethics was hard. According to the study’s conclusions, the government and educational institutions must act to address these issues and advance examination ethics.